Mechanical Integrity Analysis of a Printed Circuit Heat Exchanger with Channel Misalignment - Simanjuntak, Armanto P.; Lee, Jae Young (Applied sciences, 2020)
Printed circuit heat exchangers (PCHEs), which are used for thermal heat storage and power generation, are often subject to severe pressure and temperature differences between primary and secondary channels, which causes mechanical integrity problems. PCHE operation may result in discontinuity, such as channel misalignment, due to non-uniform thermal fields in the diffusion bonding process. The present paper analyzes the mechanical integrity, including the utilization factors of stress and deformation under various channel misalignment conditions. The pressure difference of the target PCHE is 19.5 MPa due to the high pressure (19.7 MPa) of the steam channel in the Rankine cycle and the low pressure (0.5 MPa) of molten salt or liquid metal in the primary channel. Additionally, the temperature difference between channels is around 25 °C, however the average temperature is around 500 °C. The PCHE has a relatively large primary channel measuring approximately 3 x 3 mm, and a steam channel measuring 2 x 1.5 mm. The finite element method (FEM) is applied to determine the stress by changing the misalignment to below 30% of the primary channel width. It was found that the current PCHE is operable up to 700 °C in terms of the ASME code under these design conditions. Additionally, the change of utilization factor due to the misalignment increases, but is still under the ASME acceptance criteria of 700 °C; however, it violates the criteria at 725 °C, which is the allowable temperature condition. Therefore, the mechanical integrity of the PCHE with low-pressure molten salt or liquid metal and a high-pressure steam channel is acceptable in terms of utilization factor.